Fabrication and electrical characterization of new materials for metal-oxide-semiconductor technology - Malaguti, Carlos Augusto Zan [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The Metal-Oxide-Semiconductor (MOS) technology has played a key role in the IC industry since its inception due to its excellent characteristics in digital applications, high scalability, ease of manufacturing processes, among others [1]. However, as early as the 21st century, MOSFET (Metal Oxide Semiconductor Field Effect Transistor), one of the most important devices of MOS technology, had been suffering some unwanted effects caused by the extreme miniaturization of integrated circuits. This facilitated the rise of another technology, Silicon-On-Insulator (SOI), which was more attractive to some applications, further simplifying manufacturing processes and performing better. Thus, it is now known that high performance SOI substrate-based MOS circuits are critical to any advanced electronic system. In the evolving context of integrated circuits, alternative semiconductor-based electronic systems (II-VI) can be a watershed, sparking a new revolution in nanoelectronics. Composite semiconductors such as zinc oxide and high dielectric constant insulators such as hafnium oxide have been very attractive in today's applications, due to its interesting physical properties, which can lead to transparent and organic-compatible electronics. Therefore, in this project, various aspects of manufacturing processes involving silicon-alternative materials will be analyzed, which will require a strong grounding in solid-state device physics and manufacturing processes, as well as study of material and electrical properties. The impact of this study is of major importance for next generation computing, including big data, cloud computing, IoT, cyber-physical systems and augmented reality, clean and renewable energy, and numerous health and fitness applications.

A tecnologia Metal-Óxido-Semicondutor (MOS), teve papel fundamental na indústria de CIs desde o início, devido às suas excelentes características em aplicações digitais, alta escalabilidade, facilidade de processos de fabricação, entre outros [1]. No entanto, ainda no início do século XXI, a tecnologia MOSFET vinha sofrendo alguns efeitos indesejados causados pela extrema miniaturização dos circuitos integrados. Isso facilitou a ascensão de uma outra tecnologia, a Silicon-On-Insulator (SOI), tendo sido mais atraente para algumas aplicações, simplificando ainda mais os processos de fabricação e apresentando melhor desempenho. Assim, sabe-se que atualmente circuitos MOS de alto desempenho baseados em substrato SOI são fundamentais para qualquer sistema eletrônico avançado. No contexto evolutivo de circuitos integrados, sistemas eletrônicos baseados em semicondutores alternativos (II-VI) podem ser um divisor de águas, protagonizando uma nova revolução na nanoeletrônica. Semicondutores composto como o óxido de zinco e isolantes de alta constante dielétrica, como o óxido de háfnio, tem se mostrado muito atraentes em aplicações atuais, inclusive apresentando propriedades físicas interessantes, podendo dar origem a eletrônicos transparentes e com compatibilidade à orgânicos. Portanto, neste projeto, serão analisados vários aspectos dos processos de fabricação envolvendo materiais alternativos ao silício, o que necessitará de uma forte base em física de dispositivos de estado sólido e processos de fabricação, bem como estudo de propriedades dos materiais e elétrica. O impacto deste estudo é de grande importância na computação de próxima geração, incluindo big data, computação em nuvem, IoT, sistemas ciber-físicos e realidade aumentada, energia limpa e renovável, além de inúmeras aplicações na área da saúde e condicionamento físico.
Fabricação e caracterização elétrica de novos materiais para tecnologia de metal-óxido-semicondutor
Keywords: Metal oxide semiconductors; Nanoelectronics; Semiconductors; Telecommunication